Battery provided with thermal management system comprising phase change material

By using layered heat storage units and composite materials of solid-liquid or solid-solid-solid PCM in the battery thermal management system, combined with intelligent microfluidic regeneration system, the problems of battery temperature unevenness and thermal runaway in the prior art are solved, and more efficient thermal management effects are achieved.

CN119908046APending Publication Date: 2025-04-29PARIS 12 VAL DE MARNE UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380052434.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-10
Filing Date
2023-05-09
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing battery thermal management systems are unable to effectively adapt to the unique thermal behavior of each battery cell, resulting in temperature inhomogeneity and risk of thermal runaway.

Method used

Using layered heat storage units, combined with solid-liquid or solid-solid-solid phase change material (PCM), precise thermal management for each heat zone is achieved through intelligent microfluidic regeneration systems and microfluidic thermal control circuits.

Benefits of technology

The battery temperature is uniformized, the risk of thermal runaway events is reduced, and the battery life and performance stability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119908046A_ABST
    Figure CN119908046A_ABST
Patent Text Reader

Abstract

The present invention relates to a battery comprising one or more electrochemical cells and a solid-liquid phase change material composite, the battery comprising a plurality of modules, each module having a given composite, the modules having: a separate configuration in which each module has an opening for enclosing a portion of the cell inserted into the opening, the battery is surrounded along its height by a plurality of individual modules stacked one on top of another, where at least two modules have different composite materials, this individual configuration being implemented for one or more batteries; and / or having a collective configuration in which each collective module has a plurality of openings for surrounding a portion of a plurality of cells inserted into the openings, the cells being surrounded along their height by a plurality of horizontal collective modules stacked one on top of another, with at least two modules having different composite materials; alternatively, the battery N is surrounded over its entire height by a single Nth vertical assembly module made of a composite material N, and the battery N + 1 adjacent to the battery N is surrounded by a single N + 1th vertical assembly module made of a composite material N + 1 different from the composite material N.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] manual

[0002] The present invention relates to the technical field of batteries and may relate to any type of battery, in particular for example a lithium-ion (Li-ion) battery.

[0003] The battery may be, for example, a battery used for energy storage systems, telecommunication equipment, space equipment, renewable energy equipment, electronic equipment such as power inverters, electric vehicles, and the like.

[0004] The present invention is particularly suitable for use in electric vehicle batteries.

[0005] Electric vehicles are understood to mean in particular vehicles equipped with an electric motor and a battery (BEV, battery electric vehicle), rechargeable hybrid vehicles equipped with an internal combustion engine and an electric motor, the battery of which can be recharged by connection to an external power source (PHEV, plug-in hybrid vehicle). Electric vehicles are understood here to mean two- or four-wheeled vehicles, scooters, passenger cars, commercial vehicles and public transport vehicles such as buses.

[0006] Lithium-ion (Li-ion) batteries are currently the most widely used in electric vehicles. A Li-ion battery is a group of Li-ion cells connected in series or in parallel in a module. The cells can be cylindrical, prismatic or pouch-shaped (pouch cells). Recent advances in lithium-ion batteries have led to a dramatic drop in battery prices and an increase in driving range.

[0007] To increase the range of electric vehicles, manufacturers have increased the amount of energy stored on board, either by increasing the size of the battery pack or by increasing the energy density of the battery, which today can be as high as 60 kWh and between 80 kWh and 100 kWh in some of the highest range models. The range of electric vehicles varies depending on the vehicle and driving conditions, but the energy density of the batteries means that they can be driven for at least 200 km in all conditions, with most everyday vehicle use not exceeding 100 km.

[0008] To reduce charging time, manufacturers are increasing the power of chargers from 100kW to 400kW, which translates into charging rates ranging from 1.5C to 10C at the battery cell level. However, the charging current is limited by the battery operating mechanisms, especially thermal effects and aging. Above a certain rate, increasing the charging current can lead to battery heating rather than reducing charging time. Fast charging can cause degradation of lithium-ion batteries through various mechanisms, including lithium plating, electrolyte degradation via the growth of passive layers (solid electrolyte interfaces), and mechanical degradation of electrodes.

[0009] Increased temperatures in Li-ion batteries can also lead to thermal runaway in one of the battery's cells, with a domino effect on other cells. Thermal runaway manifests as an increase in battery temperature, which accelerates exothermic reactions, leading to further increases in the battery's internal temperature, with the risk of liquid electrolyte leakage, chemical release, fire or explosion.

[0010] Lead-acid batteries are widely installed in vehicles in the railway, automotive, aircraft and satellite industries. Lead-acid batteries are a group of lead-sulfuric acid cells connected in series. Lead-acid batteries are also very sensitive to extreme temperatures. In hot weather, they release more energy than in normal temperature ranges. Heat causes loss of electrolyte in the battery, resulting in increased discharge and eventual failure.

[0011] Battery temperature control is therefore very important and is ensured by a Battery Thermal Management System (BTMS), which can be classified according to two main categories: active management systems and passive management systems.

[0012] Hybrid thermal management systems are also known, which include passive and active means. BTMS can also be divided into five categories based on the cooling means used: air, liquid, phase change material (PCM), heat pipe, refrigerant compound. Active management systems require power using forced convection or circulation of a heat transfer liquid.

[0013] The present invention more particularly relates to a battery thermal management system using a solid-liquid or solid-solid PCM.

[0014] A review of PCMs considered for battery thermal management was presented by Liu et al. in 2020 (Phase Change Materials Application in Battery Thermal Management System: A Review, Materials 2020, 13, 4622).

[0015] The thermal state of a battery depends on the individual thermal behavior of each battery cell and the collective thermal behavior of all cells of the battery.

[0016] Technical solutions currently exist, but they are unsatisfactory because they are based on plate exchangers with a flow of heat transfer fluid which do not take into account the individual behavior of each cell.

[0017] For example, Bloch et al. (Batteries Li-ion, du présent au futur [Li-ion Batteries, now and into the future], EDP 2020), a thermal management system for motor vehicle batteries using PCM exists only as a prototype, while BTMS for commercially available motor vehicles use other thermal management means, such as air cooling or cooling via contact with a liquid circulating in a cold plate.

[0018] The present invention aims to solve this first main technical problem.

[0019] When the phase change material is a solid-liquid phase change material, the present invention also aims to solve the following second technical problem.

[0020] El Idi et al. proposed the use of paraffin RT27 / aluminum foam composites (Hybrid cooling based battery thermal management using composite phase change materials and forced convection, Journal of Energy Storage, 2021, 102946), or the use of composites based on paraffin RT27 and aluminum, nickel or copper foam (A numerical investigation of the effects of metal foam characteristics and heating / cooling conditions on the phase change kinetic of phase change materials embedded in metal foam, Journal of Energy Storage, Elsevier, 2019, 26; A passive thermal management system of Li-ion batteries using PCM composites: Experimental and numerical investigations, International Journal of Heat and Mass Transfer, Vol. 169, April 2021, 120894).

[0021] Zhengyuan et al. proposed the use of paraffin / expanded graphite composites in a battery thermal management system (BTMS), which also includes cooling via water circulation through microchannels (Thermal performance of thermal management system coupling composite phase change material to water cooling with double s-shaped micro-channels for prismatic lithium-ion battery, Journal of Energy Storage, 2022, 103490).

[0022] Liquid-solid PCMs offer the possibility to store and release large amounts of heat in a small volume during phase change processes.

[0023] However, liquid-solid PCMs have a number of disadvantages that complicate their use in battery thermal management systems. The main disadvantages of PCMs are their low thermal conductivity, the significant risk of liquid PCM leaking into the battery, the need for PCM regeneration (solidification), and the volume differences of the PCM as it changes phases. In addition, the use of PCMs increases the weight and cost of the battery.

[0024] invention

[0025] The object of the present invention is to provide a battery thermal management system which does not have the disadvantages of previously proposed systems.

[0026] The invention is based on exploiting the thermodynamic properties of phase change materials (PCM), primarily their ability to store and release thermal energy at a constant temperature. This property makes it possible to conceive a very precise control of the wall temperature of the PCM, to ensure greater temperature uniformity within the cells and accumulator modules. Heat absorption also allows greater autonomy by avoiding the need for expensive, energy-intensive active systems.

[0027] The development of this innovative system is based on stratified thermal storage units.

[0028] The invention allows a thermal management for each thermal zone that is adapted both to the individual thermal behavior of the cells and to their collective thermal behavior. It is based on the installation of an initial thermally activated composite material that can be coupled to a smart microfluidic regeneration system.

[0029] Advantageously, the proposed system is coupled to a microfluidic thermal control loop based on a heat transfer liquid. For example, each PCM stratum (layer) can have a circuit independent of the other circuits. The same heat transfer fluid circulates in each circuit, with a controlled temperature and an exchange coefficient (h) adapted to the power to be dissipated. To achieve this, an optimized cooling circuit is connected to an intelligent thermal control system to ensure the regeneration of the PCM in each layer according to the thermal cycle. This solution ensures that the temperature of the battery (accumulator) is homogenized and that conditions that could lead to a battery thermal runaway event can be mitigated.

[0030] To this end, according to a first aspect, the present invention proposes a battery comprising one or more electrochemical cells and a composite material based on one or more solid-liquid or solid-solid PCMs, the composite material being configured to form a thermal management system for maintaining the temperature of the one or more electrochemical cells in operation at a value below a given temperature, the composite material being thermally conductive and comprising a thermally conductive material having a leakproof structure that allows the PCM to be encapsulated when the PCM is a solid-liquid PCM, the battery comprising a plurality of modules, each module having a given composite material that is leakproof when the PCM is a solid-liquid PCM, the modules having two possible configurations, optionally combined with one another.

[0031] Encapsulation means that when the PCM is a solid-liquid PCM, the PCM is contained in a composite module in a leakproof manner. Single-layer or multi-layer microencapsulation can be used. Multi-layer microencapsulation can be accompanied by a "self-healing" effect in the event of rupture due to thermal or mechanical stress.

[0032] Advantageously, the PCM is encapsulated in a leak-proof manner, thereby allowing the PCM to remain inside the structure during its phase change without any leakage or loss of the PCM.

[0033] Advantageously, the encapsulation of the PCM allows the PCM to be thermally conductive so as to facilitate heat transfer.

[0034] Advantageously, the package is designed as a module with openings through which the batteries can pass. This design allows the PCM of the package to be placed as close as possible to the batteries and arranged according to their thermal and mechanical characteristics. Thanks to this specific arrangement of the PCM according to its capabilities, it is possible to obtain the desired temperature during battery operation, control the mechanical behavior, especially in the vicinity of the batteries, and avoid possible liquid leaks.

[0035] In a first configuration, referred to as a single configuration, each single module has an opening allowing each single module to surround a portion of an electrochemical cell inserted into the opening, the electrochemical cell being surrounded along its height by a plurality of single modules stacked one on top of another, wherein at least two modules have different composite materials, this single configuration being implemented for only one or more batteries.

[0036] In a second configuration, referred to as an aggregate configuration, each aggregate module has a plurality of openings, allowing each aggregate module to enclose a portion of a plurality of electrochemical cells inserted into the openings in two arrangements.

[0037] Advantageously, the battery has air and / or liquid micro-exchangers comprising conductive plates and air and / or liquid micro-circuits in the conductive plates, allowing separation of the modules and regeneration of the PCMs, the micro-exchangers being configured to provide a thermally conductive bridge between the PCMs.

[0038] Advantageously, the battery has air and / or liquid micro-exchangers along the vertical and horizontal plates, in particular on the end plates outside the battery, in order to carry the heat out of the battery.

[0039] Advantageously, the plates are aligned with and / or perpendicular to the electrochemical cells and in contact with each other in order to carry heat away from the battery.

[0040] Advantageously, the battery has air and / or liquid micro-exchangers along plates, which are parallel and / or perpendicular to each other along the length of the PCM modules, which plates are in contact with each other in order to carry the heat extracted by the PCM out of the battery, and it is particularly advantageous to have internal plates located between the PCM modules in order to separate them, and these internal plates are in contact with vertical plates located outside the PCM modules.

[0041] Advantageously, the exchanger is a hybrid exchanger and comprises a conductive plate having a phase change material and microchannels within its thickness.

[0042] Advantageously, the plates are equipped with a system to control the direction of the flow, with valves to control the flow rate, and the plates can have the same or different coefficients of performance (KPI).

[0043] Advantageously, the plate is equipped with two air / liquid flow circuits or first liquid / second liquid flow circuits.

[0044] In a first arrangement, the cell is surrounded in its height by a plurality of horizontally assembled modules stacked one on top of the other, wherein at least two modules have different composite materials.

[0045] In the second arrangement, battery N is surrounded over its entire height by a single Nth vertical assembly module composed of composite material N, and battery N+1 adjacent to battery N is surrounded by a single N+1th vertical assembly module composed of composite material N+1 different from composite material N.

[0046] When a solid-liquid phase change material is used, the leakproof composite material herein means a composite material comprising a solid-liquid PCM from which the PCM in its liquid state is substantially unable to escape.

[0047] For example, the composite material has very low porosity, particularly very low interconnected porosity.

[0048] In some embodiments, the PCM is encapsulated in the composite material, in particular microencapsulated in the composite material.

[0049] In other optionally combined embodiments, the composite material is enclosed in an advantageously leakproof wall, for example made of a metal alloy.

[0050] According to various embodiments, when the phase change material is a solid-liquid phase change material, the leakage-proof composite material is selected from composite material A, composite material B or composite material C.

[0051] Composite material A comprises a thermally conductive foam having at least one PCM, which foam is advantageously encapsulated in a leakproof layer or in composite material B or in composite material C.

[0052] Composite material B comprises a matrix having at least one polymer with thermally conductive fillers and at least one PCM.

[0053] Composite material C comprises a matrix having at least one polymer with at least one PCM microencapsulated by a thermally conductive material and which allows the PCM to be contained during its change of state.

[0054] Advantageously, the battery comprises one or more compartments for accommodating the module and the electrochemical cell and adapted to their shape, the compartments having outer walls adapted to the outer periphery of the module and inner walls sized to be in contact on one face with each inner wall of the opening of the module and on another face with the outer periphery of the electrochemical cell.

[0055] Advantageously, the battery has air and / or liquid micro-exchangers which allow the modules to be separated and the PCM to be regenerated (freezed). The micro-exchangers are advantageously configured to provide a heat conducting bridge between the PCMs.

[0056] In some embodiments, the micro-exchanger comprises a plate forming at least one of the walls of the one or more different compartments.

[0057] In some specific embodiments, the shape of the plates is configured to allow them to be positioned perpendicular to the height of the electrochemical cells in one or more compartments without blocking the openings of the module.

[0058] In some specific embodiments, the shape of the plates is configured to allow them to be positioned between adjacent electrochemical cells parallel to the height of the electrochemical cells in one or more compartments.

[0059] Advantageously, the composite material surrounding the electrochemical cell at the center of the battery is designed to have a greater latent heat than the composite material at the edge of the battery.

[0060] Alternatively or in combination, the composite material surrounding the electrochemical cell at the center of the battery includes a thermally conductive material having a greater thermal conductivity than the thermally conductive material of the composite material at the edge of the battery.

[0061] Advantageously, the electrochemical cells are distributed in groups of adjacent electrochemical cells and, for at least one group of adjacent electrochemical cells, at least two different horizontal aggregation modules surround along their height all adjacent electrochemical cells of the group.

[0062] The horizontal assembly modules are selected for each group of adjacent electrochemical cells according to the following possibilities:

[0063] an aggregate module comprising composite material A and an aggregate module comprising composite material B; or

[0064] an aggregate module comprising composite material A and an aggregate module comprising composite material C; or

[0065] An assembly module comprising a composite material B having compositional variations in the polymer matrix and / or conductive fillers and / or different PCMs; or

[0066] An assembly of modules comprising composite materials C having compositional variations in the polymer matrix and / or different microencapsulated PCMs and / or different thermally conductive microencapsulated materials.

[0067] Advantageously, the air / liquid micro-exchanger has plates and air / liquid micro-circuits in the plates, the plates having openings through which the power chemical cells pass.

[0068] In some embodiments, the battery has three horizontally assembled modules having at least two different composite materials.

[0069] In some embodiments, the electrochemical cells are distributed in groups of electrochemical cells, each group of electrochemical cells having the same vertical assembly module over the entire height of the group, which is different from the vertical assembly module of at least one other group of electrochemical cells over the entire height of the group. The vertical assembly module is selected according to the following possibilities:

[0070] an aggregate module comprising composite material A and an aggregate module comprising composite material B; or

[0071] an aggregate module comprising composite material A and an aggregate module comprising composite material C; or

[0072] An assembly module comprising a composite material B having compositional variations in the polymer matrix and / or conductive fillers and / or different PCMs; or

[0073] An assembly of modules comprising composite materials C having compositional variations in the polymer matrix and / or different microencapsulated PCMs and / or different thermally conductive microencapsulated materials.

[0074] Advantageously, the accumulator has different individual modules and / or different aggregate modules stacked one on top of the other in order to create horizontal and vertical compartments around the electrochemical cells.

[0075] In some embodiments, the battery comprises a plurality of electrochemical cells, each cell being individually surrounded over its entire height by a separate module comprising composite material A, composite material B or composite material C and PCM, the composite material being selected for each cell according to its position relative to the other electrochemical cells in the battery.

[0076] Advantageously, the microcircuits differ according to the module surrounding the electrochemical cell and / or according to the position of one or more electrochemical cells in the module.

[0077] Advantageously, next to the group of electrochemical cells surrounded by the composite material, there is at least one group of electrochemical cells without the composite material.

[0078] Advantageously, the conducting plates are located at end portions of the electrochemical cells.

[0079] The thermally conductive foam is advantageously selected from the following list: aluminum foam, copper foam, nickel foam, graphite-based foam, all thermally conductive foams.

[0080] The conductive filler or conductive material encapsulating the PCM is advantageously selected from the following list: fins, expanded graphite, thermally conductive fillers derived from aluminium recycling, copper, aluminium nitride, nano-silicon dioxide.

[0081] The polymer is advantageously selected from the following list: HDPE (high density polyethylene), LDPE (low density polyethylene), SEBS (polystyrene-b-poly(ethylene-butylene)-b-polystyrene), SEPS (poly(styrene ethylene propylene styrene)) or SEP (poly(styrene-b-ethylene-co-propylene)), PU (polyurethane), PEG (polyethylene glycol), PP (polypropylene), POE (polyethylene octene co-elastomer), SBS (styrene butadiene styrene), EPDM (ethylene propylene diene monomer), recycled polymers, biopolymers (e.g. lignocellulosic polymers, chitosan, silicates, clays, etc.).

[0082] Polymers can be combined to form composite materials to fulfil several functions:

[0083] - Encapsulated PCMs "Shape Stable Phase Change Materials (SSPCMs)", e.g. Karkri et al., Polymer Testing 46 (2015), Thermochimica Acta 614 (2015) 218-225, Energy Conversion and Management, Vol. 77, January 2014,

[0084] Pages 586-596.

[0085] - Increased "PCM stable shape" rate.

[0086] - Increased rigidity / softness (Karkri et al., Applied Thermal Engineering, Vol. 171, May 5, 2020, 115072).

[0087] The PCM is advantageously selected from the following list: RT paraffin, hydrated salts, hexadecane,

[0088] The solid-solid PCM may be selected from the following list: PEG4000, PEG6000, PEG8000, PU-SSPCM (PEG / 4',4-diphenylmethane diisocyanate (MDI)), polystyrene-g-PEG6000, sorbitol / dipentaerythritol / inositol / PEG.

[0089] Advantageously, the composite material is chosen so that the temperature of the electrochemical cell during operation is below a given temperature, for example 40°C.

[0090] In some embodiments, the walls of one or more compartments comprise different materials or thermally conductive composite materials.

[0091] According to a second aspect, the present invention proposes a battery comprising one or more electrochemical cells and a composite material based on one or more solid-liquid PCMs, the composite material being configured to form a thermal management system for maintaining the temperature of one or more electrochemical cells in operation at a value below a given temperature, when the phase change material is a solid-liquid phase change material, these composite materials are selected from composite material A, composite material B and composite material C, composite material A comprises a thermally conductive foam having at least one PCM, advantageously encapsulated in a leak-proof layer or in composite material B or in composite material C, composite material B comprises a matrix having at least one polymer having a thermally conductive filler and at least one PCM, composite material C comprises a matrix having at least one polymer having at least one PCM microencapsulated by a thermally conductive material.

[0092] Advantageously, one or more electrochemical cells are surrounded by a block of composite material A that completely surrounds and encapsulates the one or more electrochemical cells, which block of composite material A is completely surrounded and encapsulated in composite material B or by composite material C or by a thermally conductive material such as an aluminum alloy, composite material A potentially being reinforced with a thermally conductive filler.

[0093] Advantageously, composite material B or C comprises a plurality of polymers.

[0094] Advantageously, composite material B or C comprises a blend of polymers from the following list: SEBS and POE; or SBS and EPDM; or HDPE and SBS.

[0095] In a second arrangement, composite material B or C has a blend of polymers selected from the following list: SEBS, SEPS, SEP, PU, ​​PEG, PP, LDPE, HDPE.

[0096] According to a third aspect, the present invention proposes a system using a battery as described above, the electrochemical battery advantageously being a lithium ion, lithium manganese cobalt (NMC), lithium polymer (LiPo), lithium iron phosphate (LFP), lithium cobalt nickel aluminum (NCA), lithium manganese (LMO), lithium titanate (LTO), lithium air, lithium cobalt oxide (LCO), lithium sulfur (Li-S), lithium metal polymer (LMP), lithium air or lithium cobalt oxide (LCO) battery, or a sodium ion battery (Na ion), nickel cadmium battery (Ni-Cd) or nickel metal hydride battery (Ni-MH).

[0097] Additional objects and advantages of the present invention will become apparent from the following description of embodiments provided with reference to the accompanying drawings, in which:

[0098] - Figure 1 is a schematic diagram of a group of cells placed in a containing matrix, encapsulated in a diffusion matrix, according to one embodiment,

[0099] - Figure 2 is a schematic diagram of a group of cells placed in a containing matrix, encapsulated in a layered diffusion matrix, according to one embodiment,

[0100] - Figure 3 is a schematic diagram of a battery pack including a cooling plate,

[0101] - Figure 4 is based on Figure 3 An exploded view of one embodiment of a battery block,

[0102] - Figure 5 is an exploded view of an alternative embodiment of a battery block,

[0103] - Figure 6is an exploded view of another alternative embodiment of a battery block,

[0104] - Figure 7 It is available for Figures 3 to 6 A detailed view of the cooling panels in the block shown in

[0105] - Figure 8 is a schematic diagram for thermal control of the battery,

[0106] - Fig. 9 is a diagram of the experimental measurement equipment,

[0107] - Fig.10 is a view of the battery holder tube,

[0108] - Fig.11 The thermocouple is shown in Fig.10 Diagram of the installation of the battery holder tube,

[0109] - Fig.12 The figure shows the case where no PCM is used and PCM RT27 and RT27 / aluminum foam are used.

[0110] A view of temperature changes over time for the

[0111] - Fig.13 , Fig.14 and Fig.15 The results are shown for mold thicknesses of e = 3 mm, e = 5 mm, and e = 7 mm, respectively, when pure paraffin RT27 is used for thermal management, and the thermal conductivity of the molds is shown by four thermoelectric

[0112] The temperature changes measured by T1, T2, T3, and T4,

[0113] - Fig.16 Plotted for the three PCM thicknesses discussed (3mm, 5mm, 7mm),

[0114] Battery temperature over time without forced convection using pure paraffin RT27

[0115] changes,

[0116] - Fig.17 Depicted for a thickness of 3 mm, using pure paraffin RT27, without forced

[0117] The battery temperature changes over time under the condition of flow.

[0118] - Fig.18 Depicted for a thickness of 7 mm, using pure paraffin RT27 and aluminum foam, without

[0119] Battery temperature over time with forced convection,

[0120] - Fig.19 and Fig. 20 The thickness e is 3 mm ( Fig.19 ) and thickness e is 7mm( Fig. 20 ) of pure paraffin RT27 record temperature (T1, T2, T3, T4) at any time

[0121] The changes between

[0122] - Fig.21 The cell surface measured by thermocouple T1 is shown for the different thicknesses studied.

[0123] The temperature changes with time,

[0124] - Fig. 22 It is shown that for a thickness of 3 mm, without and with forced convection,

[0125] The influence of metal foam on the thermal state of the battery, in the absence of forced convection, the temperature

[0126] The measurement of T1 is shown in Fig. 22 middle,

[0127] - Fig.23 The results show that the forced convection condition has pure paraffin RT27 and AF-RT27.

[0128] The temperature change of the composite battery,

[0129] - Fig.24 The results show that for AF-RT27 composite material, e = 7 mm, the

[0130] Battery temperature change over time under forced convection,

[0131] - Fig.25 Shows when the module is operated without a thermal management system (no PCM)

[0132] The change of battery temperature and heat flux when

[0133] - Fig.26 and Fig. 27 is similar to Fig.25 depiction of a system in which there is no air convection or

[0134] Use with air convection. Summary of the invention

[0135] According to a first aspect, the present invention proposes a battery comprising one or more electrochemical cells and a composite material based on solid-liquid or solid-solid PCM, the composite material being configured to form a thermal management system for maintaining the temperature of the one or more electrochemical cells in operation at a value below a given temperature, the composite material being thermally conductive when the phase change material is a solid-liquid phase change material, and comprising a thermally conductive material having a structure that allows the PCM to be encapsulated when the phase change material is a solid-liquid phase change material, the battery comprising a plurality of modules, each module having a given composite material, the modules having two possible configurations, optionally combined with each other.

[0136] According to a second aspect, the present invention provides a battery comprising one or more electrochemical cells and a composite material based on solid-liquid or solid-solid PCM, the composite material being configured to form a thermal management system for maintaining the temperature of one or more electrochemical cells in operation at a value below a given temperature, when the phase change material is a solid-liquid phase change material, these composite materials are selected from composite material A, composite material B and composite material C, composite material A comprises a thermally conductive foam having at least one PCM, advantageously encapsulated in a leak-proof layer or in composite material B or in composite material C, composite material B comprises a matrix having at least one polymer having a thermally conductive filler and at least one PCM, composite material C comprises a matrix having at least one polymer having at least one PCM microencapsulated by a thermally conductive material.

[0137] Advantageously, the thermal management system is a layered energy absorber for battery cooling.

[0138] Advantageously, the thermal management system is a universal thermal control system in the form of a "3D cold plate".

[0139] Advantageously, the thermal management system is a PCM hybrid cooling system with regenerative liquid, allowing battery life to be significantly improved.

[0140] Advantageously, the layered absorber also relates to thermal battery management systems for urban electric transportation, such as bicycles, scooters and motorcycles.

[0141] Advantageously, the thermal conductivity and heat storage capacity of the system can be varied depending on the heat source to be controlled.The thermal management system also provides flexibility in shaping (horizontally and / or vertically layered), choice of PCM and amount of conductive filler to be used. DETAILED DESCRIPTION

[0142] In the following description, three types of composite materials are advantageously used, and the composite materials are referred to as composite material A, composite material B, and composite material C.

[0143] When the phase change material is a solid-liquid phase change material, the composite material A comprises a thermally conductive foam, such as a metal foam, which contains at least one phase change material (PCM) and a leakproof material. The metal foam is, for example, aluminum foam, copper foam or nickel foam, graphite-based foam, all thermally conductive foams.

[0144] When the phase change material is a solid-liquid phase change material, the composite material B comprises a polymer matrix having one or more polymers and at least one phase change material (PCM), the matrix advantageously comprising a thermally conductive filler.

[0145] Composite material C comprises a polymer matrix having one or more polymers and at least one encapsulated phase change material (PCM), advantageously encapsulated in a thermally conductive material, the PCM advantageously being microencapsulated.

[0146] Advantageously, the microencapsulation of the three composite materials is a single-layer or multi-layer encapsulation.

[0147] Advantageously, the multilayer microencapsulation is accompanied by a "self-healing" effect in the event of rupture due to, for example, thermal or mechanical stress.

[0148] Advantageously, in the event of thermal runaway (eg, fire), the multilayer microencapsulation is accompanied by a "flame retardant" effect.

[0149] Composite material A

[0150] The composite material A is obtained, for example, by vacuum impregnation using the following method.

[0151] Solid-state PCM and metal foam are cascaded into a Pyrex glass mold before being placed in an oven.

[0152] The oven is then evacuated while the PCM remains in a solid state. The vacuum makes it possible to remove the air contained in the pores of the metal foam.

[0153] The oven was then heated for 140 minutes to a temperature above the melting temperature of the PCM to ensure that the metal foam was immersed in the liquid PCM.

[0154] The pressure in the oven is then increased, for example from 0.6 mbar to atmospheric pressure.

[0155] When the oven is at atmospheric pressure, the mold is removed from the oven and cooled, for example in a climate chamber at a fixed temperature.

[0156] Once the PCM is completely solidified, the product is removed from the mold.

[0157] The PCM impregnation process is evaluated by calculating the degree of impregnation, which is advantageously close to 100%.

[0158] The degree of impregnation α of the investigated composites is shown in Tables 1, 2 and 3. These results demonstrate the success of the vacuum impregnation process.

[0159]

[0160]

[0161] Table 1. Impregnation degree of metal foam / RT21 composites

[0162]

[0163] Table 2. Impregnation degree of metal foam / RT27 composites

[0164]

[0165] Table 3. Impregnation degree of metal foam / RT35HC composites

[0166] Composite material B

[0167] The composite material B is obtained, for example, as follows.

[0168] First, PCM is dissolved in a solvent at 80° C., and then SEBS (polystyrene-b-poly(ethylene-butylene)-b-polystyrene) and LDPE (low density polyethylene) are added to the solution until the mixture is uniform. PCM is paraffin wax, specifically paraffin wax RT42.

[0169] Then gradually add expanded graphite.

[0170] Ultrasonic treatment is applied, for example, at 100 W for 30 minutes to break up graphite aggregates and ensure uniform dispersion of the conductive filler in the mixture.

[0171] To evaporate the solvent, the resulting mixture was placed under a fume hood at a temperature of about 120°C.

[0172] The composite is then dried in an oven, for example at 130°C overnight.

[0173] Finally, the mixture is hot-pressed in a steel mold using a hot press, for example, at 130° C. for 10 minutes.

[0174] Table 4 shows examples of mixtures.

[0175]

[0176]

[0177] Table 4: Composition of SEBS / hexadecane / LDPE / GE composites .

[0178] Composite Material C

[0179] The composite material C is obtained by, for example, dispersion as follows.

[0180] A known amount of polymer (eg SEBS / LDPE) is dispersed in a solvent containing thermally conductive PCM microcapsules.

[0181] Microcapsules are made, for example, from polymeric materials of natural, semisynthetic or synthetic origin.

[0182] Microencapsulation is achieved, for example, via interfacial polymerization or spray drying. The spray drying process involves forming a solution, suspension or emulsion containing a polymer and PCM, which is sprayed by pneumatic, ultrasonic or rotary nozzles to form an aerosol. During spraying, a stream of air or nitrogen is used to form solid microcapsules after evaporation in a drying chamber.

[0183] The container containing the solvent and PCM microcapsules is placed on a hot plate. Heating under reflux is used to heat the reaction mixture. Reflux prevents loss of reagents or products through evaporation.

[0184] The microcapsules are gradually incorporated into the polymer via magnetic stirring. Stirring is maintained at reflux, for example for about 60 minutes, to ensure that the microcapsule PCM is well dispersed in the LDPE / SEBS.

[0185] Additional SEBS is added while stirring, for example, for 30 minutes.

[0186] As the temperature rises, some of the chemicals evaporate. These chemicals then rise in a water cooler. Cold water flows continuously through this cooler; upon contact with the walls, the gas cools and liquefies in the form of droplets on the walls of the cooler, eventually falling back into the container. To evaporate the solvent, the resulting mixture is placed under a fume hood at a temperature of about 120°C.

[0187] The composite material is then placed in an oven, for example at 120°C overnight.

[0188] For shaping, the mixture is hot-pressed in a steel mold using a hot press, for example at 130° C. for 10 minutes.

[0189] Table 5 shows examples of PCM microcapsule mixtures.

[0190]

[0191] Table 5: Composition of SEBS / PCM / LDPE composites

[0192] Possible implementations

[0193] Figure 1 An arrangement of a composite material according to a first embodiment is shown.

[0194] Figure 1Schematically shown are electrochemical cells 10 which are cylindrical in shape. These are, for example, 18650 cells with a diameter of 18 mm and a length of 65 mm, or 26650 cells with a diameter of 26 mm, or 2170 cells.

[0195] exist Figure 1 , a group of seventy cells is schematically depicted, with the electrical connections omitted for simplicity.

[0196] The number of cells depends in particular on the intended use of the battery (e.g. two-wheeled vehicle, car, truck). For example, forty-six cells can be connected in parallel to form a battery pack, the battery comprising two modules, each module comprising about twenty groups of cells, the modules and the groups being connected in series.

[0197] The battery is, for example, a Li-ion battery.

[0198] In the embodiment shown, the cells 10 are substantially equidistant and arranged in a square grid.

[0199] In the embodiment shown, the space present between the cells 10 is occupied by the composite material A over nearly the entire height of the cells.

[0200] Advantageously, the composite material A completely surrounds all the cells 10 .

[0201] In one embodiment, the composite material A contains a thermally conductive filler.

[0202] The composite material A block 11 including the battery 10 is contained in a case 12 formed of a mass of the composite material B or a mass of the composite material C or a heat conductive material such as an aluminum alloy.

[0203] Advantageously, the shell 12 completely surrounds the composite material A.

[0204] The shell 12 forms a container that limits the risk of leakage of the liquid-phase PCM contained in the composite material A.

[0205] The shell 12 is thermally conductive and promotes the regeneration (solidification) of the PCM contained in the composite material A.

[0206] Figure 2 An alternative embodiment is depicted. In this alternative, the battery pack 10 is, for example, a reference Figure 1 The battery described, and the group of batteries 10 is contained in a layered shell, the layered shell includes a first layer 13, a second layer 14 and a third layer 15 of a composite material.

[0207] Each of the three layers 13 , 14 , 15 may be formed from a mass of composite material A, a mass of composite material B or a mass of composite material C.

[0208] In one embodiment, one layer (eg, second layer 14) is formed from composite material A and the other two layers are formed from two masses of composite material B, the two layers of composite material B comprising different polymer matrices and / or different conductive fillers and / or different PCMs.

[0209] In another embodiment, one layer (eg, second layer 14) is formed from composite material A and the other two layers are formed from two masses of composite material C, the two layers of composite material C comprising different polymer matrices and / or different microencapsulated PCMs and / or different microencapsulated materials.

[0210] In the depicted embodiment, the three layers 13 , 14 , 15 are substantially planar and of equal thickness and extend substantially perpendicularly to the axis of elongation of the cell 10 .

[0211] Advantageously, the number of layers is greater than 2. Advantageously, the number of layers is adapted to the thermal conditions of the battery.

[0212] In other embodiments, the three layers 13 , 14 , 15 have different thicknesses from each other. For example, the middle layer 14 is thicker than the lower layer 13 and the upper layer 15 .

[0213] In other embodiments, the three layers 13, 14, 15 extend substantially parallel to the axis of elongation of the cell 10. For example, the layer 14 advantageously surrounds the cell in the center of a group of cells.

[0214] The properties of the composite material used for the three layers are advantageously different. For example, one of the layers has a higher thermal conductivity than the other two layers, or for a PCM has a higher phase transition temperature.

[0215] In other embodiments, the shell comprises two layers or more than three layers.The arrangement of the different layers of composite material in the shell forms a layered arrangement, each layer being able to be adapted to the thermal characteristics of the battery, in particular at a given height along the elongated axis of the battery.

[0216] The layered shell forms a container, limiting the risk of leakage of the liquid phase PCM contained in composite material A.

[0217] The stratified shell is thermally conductive and promotes the regeneration of the PCM contained in the composite material A, taking into account the thermal gradient along the height of the cell 10 .

[0218] Figure 3 A battery block including a case 20 , at least one phase change material 21 contained in the case 20 , and a cooling panel 22 is shown.

[0219] The phase change material 21 may be composite material A, composite material B or composite material C, or a variation of one of these composite materials.

[0220] exist Figure 3In the depicted embodiment, the block includes nine substantially identical cylindrical cells 10 arranged equidistantly in three columns and three rows. It will be appreciated that the number of cells 10 in the block may be less than nine or greater than nine, depending on the intended application of the battery.

[0221] In one embodiment, the phase change material 21 is the same for the entire battery block.

[0222] In other embodiments, the phase change material 21 is adapted to the thermal behavior of each cell 10 of the block. For example, composite material A is used for one or more cells in the center of the block, and composite material B or composite material C is used for cells at the periphery of the block.

[0223] Figure 4 Shows Figure 3 One embodiment of a block is shown.

[0224] like Figure 4 As shown, the selection of several features makes it possible to ensure the uniformity of the temperature within the block of batteries 10 .

[0225] A first choice advantageously concerns the material of the module 23 in contact with the battery 10. Figure 4 As shown, this material of the module 23 takes the form of a parallelepiped block, forming an individual composite module provided with an axial hole 24, and can be selected for each battery 10. The material of the module 23 comprises, for example, composite material A, composite material B or composite material C. In the depicted embodiment, the material of the module 23 extends substantially along the entire height of the battery 10. In other embodiments, the material of the module 23 is formed by at least two different materials stacked along the height of the battery 10. The individual modules 23 are thus layered, allowing adaptation to any potential thermal gradient along the elongated axis of the battery.

[0226] The second option relates to the housing. This second option is advantageously combined with the first option. In the depicted embodiment, the housing is formed of three stacked elements, thereby forming compartments 25, 26, 27. Each of the compartments 25, 26, 27 can be formed of a thermally conductive material, for example a metal alloy, such as an aluminum alloy. Figure 4 In the depicted embodiment, the three compartments 25, 26, 27 are substantially identical. In other embodiments, one of the compartments is thicker than the other compartments as measured along the elongated axis of the cell 10.

[0227] A third option relates to the number and arrangement of the cooling panels 22. This third option is advantageously combined with the first option and / or the second option.

[0228] exist Figure 4In the depicted embodiment, the block includes four substantially identical cooling panels 22 extending along the height of the cells 10 between two rows and between two columns of adjacent cells 10 .

[0229] Thus, the panels 22 are arranged in two groups. In each group, the panels 22 are substantially parallel to each other. The panels of the first group are substantially perpendicular to the panels of the second group.

[0230] exist Figure 5 In an alternative embodiment of the block, the block comprises two substantially identical cooling panels 22 extending along the height of the cells 10 between two rows of adjacent cells 10. Figure 5 In this alternative embodiment, the modules 23 are collective, collectively surround a plurality of batteries 10 and include, for example, three holes for the passage of three batteries 10. The cooling plates 22 extend between the collective modules 23.

[0231] Advantageously, the modules 23 are different according to the thermal state of the battery. Advantageously, the modules 23 are different for each block within the battery.

[0232] Advantageously, the structure has a layered arrangement of modules 23. For example, the layered arrangement follows one of these combinations (from lower to upper, or from upper to lower): composite material A-composite material B-composite material C; composite material B-composite material A-composite material C; composite material A-composite material C-composite material B; composite material B-composite material B'-composite material B"; composite material C-composite material C'-composite material C"; composite material A-composite material B-composite material B'; composite material B-composite material A-composite material B'; composite material A-composite material C-composite material C'; composite material C-composite material A-composite material C'; composite material C-composite material B-composite material B'; composite material B-composite material C-composite material B'; composite material B-composite material C-composite material C'; composite material C-composite material B-composite material C'.

[0233] Advantageously, the layer of composite material consists of a mixture of at least one of the following composite materials: composite material A; composite material A'; composite material A"; composite material B; composite material B'; composite material B"; composite material C; composite material C'; composite material C". By way of example, the composite layer is: composite material A+B; composite material A+B'; composite material A+B"; composite material A+C; composite material A+C', composite material A+C"; composite material A'+B'; composite material A+B+C; composite material A+B'+C; composite material A+B+C'; composite material A+B"+C; composite material A+B'+C'; composite material A+B'+C"; or composite material A'+B'+C'.

[0234] Advantageously, the layers of composite material are different so as to ensure optimal management of the battery and allow its service life to be increased.

[0235] Advantageously, composite material X' is different from composite material X, such that composite material X' has a different composition than X having a similar structure. X may be A, B or C.

[0236] Advantageously, the composite material layers in the layered arrangement have a specific shape that allows the composite material layers to interlock. Advantageously, the specific shape is composed of a "convex" triangle, a "concave" triangle, a "convex" rectangle, a "concave" rectangle, a "convex" pyramid, a "concave" pyramid, a "convex" cone, a "concave" cone, a "convex" column, a "concave" column, etc. For example, a first layer of composite material may have a "convex" triangle on the surface in contact with the composite material layer, while a second layer of composite material has a "concave" triangle on the surface in contact with the first layer of composite material.

[0237] Advantageously, when the phase change material is a solid-liquid phase change material, the composite material layer comprises at least two leakage-proof polymers for the PCM.

[0238] Advantageously, the composite material layer comprises at least three leak-proof polymers for the PCM.

[0239] Advantageously, the composite material layer comprises at least four leak-proof polymers for the PCM.

[0240] exist Figure 6 In an alternative embodiment of the block, the block comprises two substantially identical cooling plates 22 extending perpendicularly to the elongated axis of the battery 10, the material surrounding the battery 10 being formed by three modules 23 stacked along the elongated axis of the battery 10. The panel 22 extends between two modules 23. Each module 23 is placed in a compartment 25, 26, 27.

[0241] Figure 7 The geometry of the circulation microchannels 30 in the cooling plate 22 according to one embodiment is shown. The microchannels 30 include baffles (with variable sizes) to promote heat exchange. The microchannels form heat exchange micropaths. The panel 22 allows air or coolant to circulate.

[0242] Figure 8 A hybrid thermal management system for a battery 10 is schematically shown. The battery 10 is surrounded by a sleeve formed by stacking at least two different composite materials. In the depicted embodiment, three rings 40, 41, 42 are stacked along the elongated axis of the battery, each of the rings 40, 41, 42 being able to contain composite material A, composite material B or composite material C. A coil 50 helically wound around the sleeve formed by the rings 40, 41, 42 contains a heat transfer fluid.

[0243] The panel 22 or coil 50 may be coupled to a microfluidic thermal control loop based on a heat transfer liquid.

[0244] Advantageously, each coil 50 or each material layer 23 has a circuit independent of the other circuits.

[0245] In some embodiments, the same heat transfer fluid circulates in each circuit, with a controlled temperature and an exchange coefficient adapted to the power to be dissipated. To achieve this, an optimized cooling circuit is connected to an intelligent thermal control system to ensure the regeneration of the PCM in each individual or collective module 23 according to the thermal cycle. These provisions ensure that the temperature of the battery 10 is homogenized and that conditions that could lead to a battery thermal runaway event can be mitigated.

[0246] Advantageously, the phase change material is of natural origin.

[0247] Advantageously, the concentration of PCM varies from one layer of composite material to another, while maintaining the same type of PCM.

[0248] Advantageously, the type of PCM varies from one layer of composite material to another, while maintaining the same concentration of PCM.

[0249] Advantageously, the type of PCM and the concentration of PCM vary from one layer of composite material to another.

[0250] Advantageously, at least two different types of PCM are present in the same composite layer.

[0251] Advantageously, the microencapsulation of the PCM in the composite material C is optimized according to the thermal conditions of the battery. For example, the composition of the microencapsulation may have different properties or thicknesses.

[0252] Advantageously, the microencapsulation of PCM in the composite material C has a multilayer structure. Advantageously, each layer constituting the multilayer structure has a different function.

[0253] The results obtained will refer to Fig. 9 And the following figures are presented.

[0254] Results will be presented concerning thermal phenomena in Li-ion batteries, as well as the dimensioning and optimization of a passive management system using a PCM metal foam (MF) composite material, the battery 10 being advantageously maintained at a temperature above 30°C at a load of 1C.

[0255] A test bench was developed to track the temperature changes in the Li-ion battery 10 and the heat flux it gives off when under load.

[0256] The actual amount of heat dissipated by the battery 10 is calculated using the experimental results and a calculation code developed in Matlab.

[0257] The thermal behaviors of PCM and PCM-metal foam MF composites were simulated using COMSOL Multiphysics and Matlab.

[0258] The experimental test bench is shown in Fig. 9 middle.

[0259] The investigated 2500 mAh electrochemical cell 10 was connected to a DC power supply for charging and to an active load for discharging. The cell 10 was cylindrical with a radius of 9.255 mm and a height of 70 mm.

[0260] An electromechanical relay is inserted, allowing the circuit to be opened and closed. The surface temperature of the battery 10 is measured by two T-type thermocouples. A cylindrical flux meter covers the battery 10 in order to measure the heat flux dissipated over time.

[0261] A LabVIEW program was developed to track the charge / discharge cycles of the battery. This made it possible to control relays, power supplies, and active loads simultaneously and acquire measurement data.

[0262] The studied battery was suspended to avoid heat exchange by conduction between the battery surface and the external environment.

[0263] The battery 10 studied was placed in an aluminum mold, such as Fig.10 The mold takes the form of two hollow coaxial aluminum cylinders of height h and thickness e. The two cylinders form an inner tube (containing the battery) and an outer tube.

[0264] The inner tube has the same diameter as the battery 10 .

[0265] The PCM with or without metal foam MF is inserted into the space between the inner and outer tubes.

[0266] Grooves are provided at the cell-inner tube interface to accommodate the temperature sensor and flux meter wires.

[0267] The dimensions of the molds were designed taking into account the expansion of the PCM volume. Aluminum was chosen because of its good compromise between thermal properties, density and cost. To study the impact of PCM mass, three molds with different thicknesses (3mm, 5mm and 7mm) were produced. All molds were produced using metal 3D printing.

[0268] Liquid paraffin was injected into the space designed to receive it. After filling, the assembly was cooled in a climate chamber at a set temperature of 22°C.

[0269] Before inserting the cell 10 into the mold, all connections must be secured to prevent direct contact between the aluminum mold and the cell.

[0270] In the case of metal foam MF-PCM composites, metal foam (eg, aluminum foam AF) was cut into tubes of size h*e using a laser cutting system. The tubes were filled with paraffin according to the vacuum infusion process described above.

[0271] After filling and instrumentation, the cell 10 and the mold are placed in a climate chamber. The bottom of the mold is insulated with a layer of expanded polystyrene.

[0272] To evaluate the effectiveness of using paraffin RT27 and AF-RT27 composites and their ability to absorb heat generated by the battery 10 during the charge / discharge cycle, the Fig.11 Four type K thermocouples (T1, T2, T3 and T4) arranged as shown in FIG. 5 track radial temperature variations at the interface.

[0273] Thermocouple T1 is placed between the battery 10 and the inner wall of the inner tube. Thermocouple T2 is placed between the outer wall of the inner tube and the composite material. Thermocouple T3 is placed between the composite material and the inner wall of the outer tube. Thermocouple T4 is placed on the outer wall of the outer tube.

[0274] Conducting tests and defining steady state

[0275] The tests were carried out for different currents and for a maximum voltage of 3.8 V, without a pause between two consecutive cycles. A cycle corresponds to a charge followed by a discharge. If a fully charged battery is discharged via a current of 2.5 A, it will reach its cut-off voltage after one hour of discharge. Once a steady state is reached, the test is stopped. Specifically, the temperature first increases and then tends to a constant value, which characterizes the steady state.

[0276] Battery temperature changes

[0277] Fig.12 The temperature measured by thermocouple T1 is shown as a function of time. The results are given for a mould thickness of 3 mm. For the three cases studied, namely natural convection (cell without thermal management system), paraffin RT27 and aluminium foam AF (porosity 0.93, pore density 40 PPI) - paraffin RT27 composite, the results were obtained under the same conditions, namely an imposed current of 1 C (2.6 A) for ten charge / discharge cycles of eight minutes.

[0278] In the case of thermal management using pure paraffin RT27 and paraffin / aluminum foam AF composites, the imposed temperature is 22°C. In these cases, ventilation is active to promote heat exchange between the evaporator (condenser in the case of heating) and the air inside the climate chamber.

[0279] The results show that the addition of pure PCM or MF-PCM composite significantly reduces the temperature of the cell 10. In the case of management with pure paraffin RT27 or AF paraffin RT27 composite, the steady state is reached after two cycles compared to five cycles in the natural convection case.

[0280] At steady state, the temperature of the cell 10 with natural convection reached 36.7° C., compared to 26.5° C. when pure paraffin RT27 was used, and 25.6° C. when the paraffin RT27-aluminum foam composite (0.93, 40 PPI) was used.

[0281] Pure paraffin wax RT27 reduces the temperature of the battery 10 by 10.2° C. (steady-state mean deviation), while the paraffin wax RT27-aluminum foam AF (0.93, 40 PPI) composite material reduces the temperature of the battery by 11.2° C. (steady-state mean deviation).

[0282] Temperature distribution without forced convection

[0283] In order to avoid heat losses from the battery 10 to the ambient air and to simulate the situation where the battery 10 is placed in a very confined location (battery module), tests without forced convection were performed. The assembly was placed in a climate chamber, initially in thermal equilibrium at 22°C, isolated from any heat exchange with the surrounding environment.

[0284] Fig.13 , Fig.14 and Fig.15 The variation of the temperature measured by the four thermocouples T1 , T2 , T3 , T4 in the case of thermal management with pure paraffin RT27 is shown for mold thicknesses of e=3 mm, e=5 mm and e=7 mm respectively.

[0285] exist Fig.13 , Fig.14 and Fig.15 The temperature curve measured by thermocouple T1 (battery temperature) is at a certain distance from the other three overlapping curves T2, T3, T4 (PCM temperature).

[0286] The results show that pure paraffin RT27 completely melts in the case of a thickness of 3 mm, which results in a high temperature relative to other cases. Therefore, underestimating the amount of PCM required to absorb the heat generated by the battery 10 may result in a high temperature.

[0287] The difference between the battery temperature (T1) and the wax temperature (T2) is inversely proportional to the thickness. The smallest difference is observed at a thickness of 3 mm. Increasing the thickness of the wax increases the thermal resistance due to its low thermal conductivity, resulting in a less intense heat transfer than in the case of pure solids or pure liquids.

[0288] Fig.16 The temperature variation of the cell 10 over time without forced convection is depicted for the three PCM thicknesses discussed (3 mm, 5 mm, 7 mm) using pure paraffin RT27.

[0289] In the solid phase, a lower temperature is observed for the thickness e of 3 mm compared to the other two cases. In addition, after the paraffin wax RT27 is completely melted, there is an inflection point in the curve representing the temperature change of the battery 10 .

[0290] The changes in temperature T1, T2, T3, T4 in the case of MF-PCM composites without forced convection were evaluated for thicknesses of 3 mm and 7 mm. The results are shown in Fig.17 (3mm thickness) and Fig.18 (7 mm thickness). The metal foam is aluminum foam (AF).

[0291] The results show that the addition of metal foam MF makes it possible to significantly reduce the temperature difference between the cell 10 and the MF-PCM composite by improving the effective electrical conductivity of the RT27 / metal foam composite.

[0292] For the MF-PCM composite with a thickness of 3 mm, the difference between T1 and T2 remains small, about 0.5 °C ( Fig.17 ).

[0293] For a PCM having a thickness of 7 mm, the difference between the temperature T1 of the battery and the temperature T2 of the PCM is 2.5°C in the case of pure paraffin RT27 and 1.6°C in the case of AF-RT27 ( Fig.18 ). These results are consistent with those obtained from numerical studies.

[0294] Temperature distribution with forced convection

[0295] In order to test the influence of convection on the thermal conditions of the battery 10 , ventilation was activated with the aim of ensuring a uniform temperature (22° C.) in the climate chamber.

[0296] Fig.19 and Fig. 20 The thickness e is 3 mm ( Fig.19 ) and thickness e is 7mm( Fig. 20 ) of pure paraffin RT27 to record the changes of temperature (T1, T2, T3, T4) over time.

[0297] The steady state is reached faster in the case of a thickness of 3 mm, where the thermal uniformity depends on the thickness (T2=T3).

[0298] In both configurations studied, the paraffin was not completely melted at the end of the test. This can be attributed to heat losses through forced convection.

[0299] The influence of the amount of PCM used was evaluated for the three thicknesses studied (e=3 mm, e=5 mm and e=7 mm) under imposed ambient temperature with ventilation (forced convection). The tests were carried out under the same conditions: 1C current (2.6 A), ten charge / discharge cycles for eight minutes at an ambient temperature of 22°C.

[0300] Fig.21 The temperature of the surface of the cell 10 measured by the thermocouple T1 is shown as a function of time for the different thicknesses studied.

[0301] Increasing the thickness of the PCM has a negative impact on the thermal management of the battery 10. In particular, the PCM has a low thermal conductivity, which reduces the intensity of the heat transfer to the outside. In this case, the system should be combined with an active management system (air, heat transfer fluid).

[0302] Adding the effects of metal foam and forced convection

[0303] The effect of the metal foam on the thermal state of the cell 10 was evaluated for a mold e = 3 mm without and with forced convection. The temperature T1 was measured as shown in Fig. 22 There is no forced convection.

[0304] exist Fig. 22 , it can be seen that adding the metal foam reduces the temperature of the battery 10 during the melting process. In particular, adding the conductive foam enhances the heat transfer. In principle, a greater effect should be achieved if forced convection is prevented.

[0305] To confirm or refute this, the temperature of the cell 10 with pure paraffin RT27 was compared with the temperature of the cell 10 with the AF-RT27 composite material ( Fig.23 , with forced convection). The comparison shows a steady-state temperature average deviation of about 1.2°C between the temperature of the cell 10 with pure RT27 and with the AF(0.93, 40PPI)-RT27 composite.

[0306] Fig.24 The temperature of the battery 10 is shown over time without and with forced convection for the AF-RT27 composite material, e = 7 mm. In the case of forced convection, a steady state is reached after about five cycles, while in the case of natural convection, the temperature of the battery 10 continues to rise. The temperature of the battery 10 reaches 28.5°C at the end of the test with isolation, while the temperature of the battery 10 at the end of the test with convection is 26.3°C, i.e., a temperature difference of about 2.2°C.

[0307] Thermal management of Li-ion battery modules

[0308] In this section, results obtained in the thermal management of a battery module consisting of nine Li-ion cells 10 assembled in a 3S-3P configuration are presented.

[0309] The test process corresponds to one cycle of discharging and then charging without pause. The battery module is first discharged at a constant current of 6 A to a minimum voltage of 8 V, and then charged at a current of 6 A to a maximum voltage of 12 V using the CC-CV method.

[0310] A total of twenty thermocouples and fifteen fluxmeters were used to evaluate temperature variations within the module. Only five cells 10 were installed. Before installing the fluxmeters and thermocouples, a thin layer of thermal grease was spread on the side surfaces of the cells 10 to facilitate heat transfer to the fluxmeters and reduce contact resistance.

[0311] Next, the battery 10 was placed in a climate chamber, through which the temperature was fixed at 21.5°C; the Li-ion cells were then assembled into a 3S-3P configuration while maintaining an inter-cell distance of 3 mm with the help of two 3D printed support plates.

[0312] Fig.25 The variation of the temperature and heat flux of the battery 10 is shown when the module is operated without a thermal management system (no PCM). It can be seen that the maximum temperature of the module exceeds 35°C, although the forced convection system has a constant temperature of 21°C during charging and discharging.

[0313] Thermal Management Using PCM+Metal Foam

[0314] The metal foam MF / phase change material PCM composite material is introduced into the battery support mold.

[0315] The same test as above was used (discharge-charge without pause). The temperature was maintained at 21.5°C with ventilation disabled.

[0316] The experimental results show that the maximum temperature measured inside the battery module is 27.8°C, and forced ventilation allows the temperature to be reduced to 25.22°C. It can also be seen that the center battery always has the highest temperature inside the module.

[0317] Regarding the flux density, there is no big difference when the system is loaded without air convection and when air convection is activated ( Fig.26 and Fig. 27 ).

[0318] The present invention has many advantages.

[0319] Advantageously, the present invention provides a thermal management system for batteries, particularly Li-ion batteries, which allows the battery temperature to be maintained below 40°C.

[0320] Advantageously, the invention makes it possible to provide a thermal management system for batteries, in particular Li-ion batteries, using a phase-change thermally conductive composite material, which makes it possible to maintain the temperature of the battery close to the optimal operating temperature.

[0321] Advantageously, the invention makes it possible to provide a thermal management system for batteries, in particular Li-ion batteries, using metal foam, conductive fillers and paraffin, which allows the battery temperature to be maintained between 15°C and 30°C.

[0322] Advantageously, the invention makes it possible to provide a thermal management system for batteries, in particular for lithium-ion batteries, which preserves the battery life and ensures optimal operation for as long as possible.

[0323] Advantageously, the invention makes it possible to provide a thermal management system for a battery, in particular for a lithium-ion battery, which allows the temperature distribution in the battery to be homogenized.

[0324] Advantageously, the invention makes it possible to provide a thermal management system for batteries, in particular for lithium-ion batteries, which makes it possible to increase the battery's service life and maintain its state of health.

[0325] Therefore, the present invention proposes a battery, which is provided with at least one electrochemical cell and a composite material including a solid-liquid phase change material (PCM), the battery comprising a containment matrix surrounding one or more cells and a diffusion matrix surrounding the containment matrix, the containment matrix comprising one or more composite material blocks, each composite material block surrounding at least one cell over at least a portion of its height.

[0326] The diffusion and / or containment matrix comprises at least two layers of different composite materials.

[0327] The composite material is advantageously selected from the group comprising:

[0328] - Composite material A, which comprises a thermally conductive foam containing a phase change material (PCM);

[0329] - Composite material B comprising a polymer matrix and a phase change material (PCM);

[0330] - Composite material C comprising a polymer matrix and an encapsulated phase change material (PCM).

[0331] The containment matrix surrounds one or more batteries and is therefore directly exposed to the temperature rise in the batteries, for example during rapid battery charging or intensive use of the electric vehicle. Advantageously, a conductive material is placed between the containment matrix and the batteries, for example a conductive grease.

[0332] Heating of the cell results in a phase change of the PCM used in the containment matrix.

[0333] The risk of leakage of the liquid PCM is limited by the presence of the diffusion matrix surrounding the containment matrix. Advantageously, the diffusion matrix completely surrounds and encapsulates the containment matrix.

[0334] Alternatively or in combination, when the phase change material is a solid-liquid phase change material, the composite material containing the matrix is ​​leakproof. Here, a leakproof composite material means a composite material comprising a solid-liquid PCM, and the PCM in its liquid state cannot basically escape from the composite material. For example, the composite material has a very low porosity, in particular a very low interconnected porosity. In some embodiments, the PCM is encapsulated in the composite material, in particular microencapsulated in the composite material. In other optionally combined embodiments, the composite material is encapsulated in a leakproof wall, for example made of a metal alloy.

[0335] The presence of at least two layers in the containment and / or diffusion matrix comprising different composite materials makes it possible to adapt to the inhomogeneous thermal behavior of the battery.

[0336] When the cell has an axis of elongation, the layer containing the matrix and / or the layer of the diffusion matrix extends substantially perpendicularly to the axis of elongation of the cell. This arrangement makes it possible to take into account the thermal gradients of the cell in its direction of elongation.

[0337] Advantageously, the PCMs contained in the layers of the diffusion and / or containment matrix have melting temperatures that are different from one another.

[0338] Advantageously, the containment and / or diffusion matrix comprises a thermally conductive filler, for example selected from the group comprising expanded graphite, copper and aluminium nitride.

[0339] Advantageously, the battery has air / liquid micro-exchangers that allow separation of the modules 23 and regeneration of the PCMs, the micro-exchangers being configured to provide a thermally conductive bridge between the PCMs.

[0340] Advantageously, the micro-exchanger has a shape optimized to increase the efficiency of the device (with KPI, “Key Performance Indicator”).

[0341] Advantageously, the micro-exchanger has a given flow rate and circulation speed. Advantageously, the flow rate is adapted to the shape of the micro-exchanger and / or to the thermal state of the battery and / or to the number of batteries.

[0342] Advantageously, the micro-exchangers are micro-channels in the direction of the slices and / or perpendicular to the slice planes.

[0343] Advantageously, the liquid circulating in the micro-exchanger is air, water or a heat transfer liquid. Advantageously, the liquid in the micro-exchanger is varied / selected depending on the operating temperature and operating constraints.

[0344] Advantageously, the system for actuating the circulation of a fluid is based on an overall management program, with a plurality of program input parameters: temperature, volume expansion, etc.

[0345] Additional automation systems can be associated to ensure forced regeneration at programmable times and temperatures. Regeneration can be performed for each identifiable block using a network of optimally positioned sensors and actuators managed by computer logic.

[0346] Advantageously, the system of the invention is coupled to another system. Advantageously, the system of the invention transfers thermal energy to the coupled system. Advantageously, the system of the invention is of sufficiently large size to exploit the energy gain. For example, in the case of an electric vehicle, the recovered heat is used to supplement the passenger compartment heating system.

[0347] The invention allows thermal management of each battery zone, in particular for each group of cells. The invention thus allows high temperature uniformity along the height of each cell or within a battery module. In particular, the invention makes it possible to avoid the presence of thermal gradients between the core of a battery and its periphery.

[0348] The present invention greatly reduces the risk of PCM leakage in the liquid phase.

[0349] The invention allows a battery, in particular a Li-ion battery, to be maintained at a substantially uniform temperature within an optimum operating range, advantageously between 15° C. and 35° C. for a Li-ion battery.

[0350] The thermal management system according to the invention takes the form of a layered energy absorber. Such a system is particularly suitable for the case of batteries used in electric bicycles, electric scooters and electric two-wheeled vehicles (scooters, motorcycles).

[0351] In one embodiment, the thermal management system according to the present invention is a PCM+regenerative liquid hybrid cooling system, allowing for significant improvements in battery life.

[0352] The invention is advantageously applied to electric vehicles, in particular motor vehicles or two-wheeled vehicles.

[0353] The invention also has application in the cooling of microprocessors, or the regulation of energy storage batteries in photovoltaic systems or solid hydrogen storage tanks.

[0354] Advantageously, the present invention is used in batteries for energy storage systems, telecommunication equipment, space equipment, renewable energy equipment, electronic equipment such as power converters, data centers, electric vehicles, and the like.

Claims

1. A battery comprising an electrochemical cell (10) and a composite material (21) based on one or more solid-liquid or solid-solid phase change materials (PCM), the composite material being configured to form a thermal management system for maintaining the temperature of one or more electrochemical cells (10) in operation at a value below a given temperature, Features: - the composite material (21) comprises one or more conductive materials and a leakproof structure, The anti-leakage structure allows the PCM to be encapsulated when the PCM is a solid-liquid PCM, - the battery comprises a plurality of modules (23), each module having a given composite material (21), the given composite material being leakproof when the PCM is a solid-liquid PCM, The composite module (23) has: A separate configuration, wherein each separate module (23) has an opening (24) allowing each separate module (23) to surround a portion of an electrochemical cell (10) inserted into said opening (24), the electrochemical cell (10) being surrounded along its height by a plurality of separate modules (23) stacked one on top of the other, wherein at least two modules (23) have different composite materials, said separate configuration being implemented for a plurality of cells (10); or A collection configuration, wherein each collection module (23) has a plurality of openings (24), Each assembly module (23) is allowed to surround a portion of a plurality of adjacent electrochemical cells (10) inserted into the opening (24), specifically according to one of the following two configurations: - the cell (10) is surrounded in its height by a plurality of horizontally assembled modules (23) stacked one on top of the other, wherein at least two modules (23) have different composite materials; or - a cell N is surrounded over its entire height by a single Nth vertical assembly module consisting of a composite material N, and a cell N+1 adjacent to said cell N is surrounded by a single N+1th vertical assembly module consisting of a composite material N+1 different from said composite material N, And wherein the battery has an air and / or liquid micro-exchanger, the micro-exchanger comprising a conductive plate and an air and / or liquid micro-circuit in the conductive plate (22), thereby allowing the separation of the modules (23) and the regeneration of the PCM, the micro-exchanger being configured to provide a thermal conduction bridge between the PCMs and to carry heat out of the battery.

2. Battery according to claim 1, wherein the battery has air and / or liquid micro-exchangers along plates, advantageously parallel and / or perpendicular to each other along the length of the PCM modules, the plates being in contact with each other in order to carry the heat extracted by the PCM out of the battery, particularly advantageously with inner plates between the PCM modules in order to separate them and in contact with vertical plates outside the PCM modules.

3. The battery according to any one of claims 1 and 2, wherein the exchanger is a hybrid exchanger and comprises a conductive plate having a phase change material and microchannels within its thickness.

4. The battery according to any one of claims 1 to 3, wherein the plate (22) is equipped with a system for controlling the direction of flow, the system having valves for controlling the flow rate.

5. The battery according to any one of claims 1 to 4, wherein the plate (22) is provided with two air / liquid flow circuits or first liquid flow circuits / second liquid flow circuits.

6. The battery according to claim 1, wherein the plates (22) have openings for the passage of the electrochemical cells (10).

7. The battery according to any one of claims 1 to 6, wherein the battery comprises one or more compartments (25, 26, 27) for accommodating the module (23) and the electrochemical cell (10) and matching the shape of the module (23) and the electrochemical cell (10), the compartments having: - an outer wall matching the outer periphery of said module (23), and - an inner wall dimensioned to be in contact on a first face with each inner wall of the opening (24) of the module (23) and on a second face with the outer periphery of the electrochemical cell (10).

8. The battery according to any one of claims 1 to 7, wherein the shape of the plate (22) is configured as follows: - having openings for the passage of the electrochemical cells (10) and allowing the plate to be positioned perpendicularly to the height of the electrochemical cells (10) in the one or more compartments (25, 26, 27), - or allowing the plate to be positioned between adjacent electrochemical cells (10) parallel to the height of the electrochemical cells (10) in the one or more compartments (25, 26, 27).

9. The battery according to any one of claims 1 to 8, wherein when the phase change material is a solid-liquid phase change material, the composite material is leakproof and is selected from composite material A, composite material B and composite material C, specifically defined as follows: - Composite material A comprises a thermally conductive foam with at least one encapsulated PCM, said thermally conductive foam being enclosed in one or more anti-leakage layers or in composite material (B) or in composite material (C), - composite material B comprises a matrix with at least one polymer with thermally conductive fillers and at least one encapsulated PCM, - Composite material C comprises a matrix with at least one polymer having at least one PCM microencapsulated by at least one thermally conductive material and which allows said PCM to be contained during its changes of state.

10. The battery according to any one of claims 1 to 9, wherein the composite material surrounding the electrochemical cell (10) located in the center of the battery is constructed with: - a latent heat greater than the latent heat of the composite material located at the edge of the battery; and / or a thermally conductive material having a thermal conductivity greater than that of the thermally conductive material of the composite material located at the edge of the battery.

11. The battery according to any one of claims 1 to 10, wherein the electrochemical cells (10) are distributed in groups of adjacent electrochemical cells and, for at least one group of adjacent electrochemical cells, at least two different horizontal aggregation modules (23) surround all the adjacent electrochemical cells (10) of the group along their height or a part of their height, The horizontal aggregation module (23) is selected for each group of adjacent electrochemical cells (10) according to the following possibilities: - an assembly module including composite material A and an assembly module including composite material B; or - an aggregate module including composite material A and an aggregate module including composite material C; or - an assembly module comprising a composite material B having compositional variations in said polymer matrix and / or conductive fillers and / or different PCMs; or - An assemblage of modules comprising composite materials C having compositional variations in said polymer matrix and / or different microencapsulated PCMs and / or different thermally conductive microencapsulated materials.

12. The battery according to any one of claims 1 to 11, wherein the electrochemical cells (10) are arranged as an electrochemical battery pack, Each group of electrochemical cells has, over the entire height of the group or a portion of its height, an identical vertical assembly module (23) that is different from another vertical assembly module (23) of at least one other group of electrochemical cells over the entire height of the group or a portion of its height, The vertical assembly module (23) of composite material is selected according to the following possibilities: - an assembly module including composite material A and an assembly module including composite material B; or - an aggregate module including composite material A and an aggregate module including composite material C; or - an assembly module comprising a composite material B having compositional variations in said polymer matrix and / or conductive fillers and / or different PCMs; or - An assemblage of modules comprising composite materials C having compositional variations in said polymer matrix and / or different microencapsulated PCMs and / or different thermally conductive microencapsulated materials.

13. The battery according to any one of claims 1 to 12, wherein the battery has different assembly modules (23) so as to provide horizontal and vertical compartments (25, 26, 27) around the electrochemical cell (10).

14. A battery according to any one of claims 1 to 13, comprising a plurality of electrochemical cells (10), each cell (10) being individually surrounded by a module (23) over its entire height, the composite material being selected for each cell (10) depending on its position relative to the other electrochemical cells (10) in the battery.

15. The battery according to any one of claims 1 to 14, wherein the microcircuit differs according to the module (23) surrounding the electrochemical cell (10) and / or according to the position of one or more electrochemical cells (10) in the module (23).

16. The battery according to any one of claims 1 to 15, wherein next to a group of electrochemical cells (10) surrounded by a plurality of modules there is at least one group of electrochemical cells comprising electrochemical cells (10) without modules.

17. The battery according to any one of claims 1 to 16, wherein the exchanger is adapted to the shape of the battery.

18. The battery according to any one of claims 9 to 17, wherein: - the thermally conductive foam is selected from the following list: aluminum foam, copper foam, nickel foam, graphite-based foam, all thermally conductive foams; and / or - the conductive filler or the conductive material encapsulating the PCM is selected from the following list: Fins, expanded graphite, thermally conductive fillers from recycled aluminum, copper, aluminum nitride, nano-silicon dioxide; and / or - the polymer is selected from the following list: HDPE, LDPE, SEBS, SEPS, SEP, PU, ​​PEG, PP, POE, SBS, EPDM, recycled polymers, biopolymers; and / or - The PCM is selected from the following list: RT paraffin, hexadecane, Hydrated salt.

19. The battery according to any one of claims 9 to 17, wherein the solid-solid PCM is selected from the following list: PEG4000, PEG6000, PEG8000, PU-SSPCM (PEG / 4',4-diphenylmethane diisocyanate), polystyrene-g-PEG6000, sorbitol / dipentaerythritol / inositol / PEG.

20. The battery according to any one of claims 1 to 19, wherein the composite material is selected such that the temperature of the electrochemical cell (10) during operation is below 40°C.

21. A battery according to any one of claims 7 to 20, wherein the walls of the one or more compartments (25, 26, 27) comprise different materials or thermally conductive composite materials, for example these compartments are thermally conductive composite materials with one or more PCM or hybrid microexchangers (PCM microrings) or air or liquid microexchangers.

22. The battery according to any one of claims 9 to 21, wherein the composite material B or C comprises a plurality of polymers.

23. The battery according to claim 22, wherein the composite material B or C has ● Blends of the following polymers: -SEBS and POE; -SBS and EPDM; -HDPE and SBS; ● or a blend of polymers selected from: SEBS, SEPS, SEP, PU, ​​PEG, PP, LDPE, HDPE.

24. A system using a battery according to any one of claims 1 to 23, wherein the electrochemical cell (10) is a lithium ion, lithium manganese cobalt (NMC), lithium polymer (LiPo), lithium iron phosphate (LFP), lithium cobalt nickel aluminum (NCA), lithium manganese (LMO), lithium titanate (LTO), lithium air, lithium cobalt oxide (LCO), lithium sulfur (Li-S), lithium metal polymer (LMP), lithium air or lithium cobalt oxide (LCO) battery, or a sodium ion battery (Na ion), nickel cadmium battery (Ni-Cd) or nickel metal hydride battery (Ni-MH).